A synopsis of the Centaurea soskae and triniifolia group (Centaurea sect. Acrolophus) in the Prespa area and Northern Pindos - Wagenitz, Gerhard; Bergmeier, Erwin; Gregor, Thomas; Meierott, Lenz; Shuka, Lulezim; Tan, Kit (Phytotaxa, 2018)
A synopsis of the Centaurea soskae and triniifolia group (C. sect. Acrolophus, Asteraceae) is presented. Seven taxa are recognized in the Lake Prespa area of Albania, Greece, FYR Macedonia, and the nearby mountain ranges of Galičica-Mali i Thatë and Pelister-Varnous, including an outlier in the prefecture of Grevena, N Pindos, Greece. The variation in C. soskae was studied, leading to the description of two new subspecies, subsp. albida (endemic to Albania) and subsp. aetiensis (endemic to N Pindos). Centaurea tomorosii is treated as a species separate from C. soskae, and C. galicicae as a species distinct from C. triniifolia. The lectotypification of C. campylacme and its inclusion as a subspecies in C. triniifolia is proposed. In addition, C. shumkana is described as a new species, endemic to SE Albania. The distribution of the taxa is indicated in two maps.